A Land Without Borders - Alalu, Michael; Baram, Nir (Israel, 2017)
A travelogue by Nir Baram, an Israeli writer, in the occupied territories, to examine whether the idea of" two states for two peoples" is relevant and whether there is any chance for peace.
Verzio Film Festival Submission
Keywords: Documentary films